(untitled) (Tintas. Quaderni di Letterature iberiche e iberoamericane, 2013)
Este trabajo ofrece un estudio bibliográfico sobre dieciocho textos de relaciones de comedia de la Bibloteca Universitaria de Cagliari (Cerdeña) salidos del taller sevillano de Leefdael (1717-1733), con la edición de dos pliegos conservados únicamente en este rico y poco conocido fondo de pliegos sueltos teatrales de principios del s. XVIII. This paper provides a bibliographical study on eighteen texts of “relaciones de comedia” preserved in the University Library of Cagliari (Sardinia) and produced by Leefdael Printing office at Seville between 1717-1733. It includes a bibliographical repertory and the edition of two unknown pieces of thouse broadsheets or “pliegos sueltos” at the begnining of the 18th century.